1999
DOI: 10.1080/00365519950185463
|View full text |Cite
|
Sign up to set email alerts
|

Platelets enhance neutrophil locomotion: evidence for a role of P-selectin

Abstract: It has been suggested that the accumulation of platelets at sites of vascular damage and inflammation regulates the function of leukocytes. In this study, we investigated the effects of platelets on the transmigration of neutrophil granulocytes through microporous membranes. We demonstrate that platelets markedly enhance both the random and the chemotactic migration of neutrophils. Stimulatory effects were acquired by adding paraformaldehyde-fixed platelets or the supernatants of platelets; however, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Such data argue for integrin-independent mechanisms. P-selectin promotes the accumulation and emigration of neutrophils during inflammation and thrombosis [16], and its ligand PSGL-1 is probably very important for the early neutrophil activation, including rolling along endothelial P-selectin [36,37]. The results in this study suggest a major contribution of platelet derived components to trigger the P-selectin/PSGL-1 interaction.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Such data argue for integrin-independent mechanisms. P-selectin promotes the accumulation and emigration of neutrophils during inflammation and thrombosis [16], and its ligand PSGL-1 is probably very important for the early neutrophil activation, including rolling along endothelial P-selectin [36,37]. The results in this study suggest a major contribution of platelet derived components to trigger the P-selectin/PSGL-1 interaction.…”
Section: Discussionmentioning
confidence: 64%
“…It is generally considered that an integrin-mediated firm adhesion of neutrophils to endothelial cells or platelets require a prior selectin-dependent interaction. We have recently found that the presence of adhering platelets markedly enhance both the random and the chemotactic transmigration of neutrophils, and that these effects are mediated by P-selectin and associated with increased expression of complement receptor 3 (CR3, CD18/CD11b, Mac-1 or  M  2 ) [16]. Furthermore, platelets enhance the F c -receptor mediated phagocytosis and respiratory burst in neutrophils [17].…”
Section: Introductionmentioning
confidence: 99%
“…21 Several observations suggest that platelets deposited at sites of thrombosis and vascular injury serve as surrogates for endothelium by recruiting circulating leukocytes. 14,24 Tsuji et al 25 demonstrated that platelet P-selectin directly triggers oxygen radical production in neutrophils, and we have recently shown that collagen-activated platelets stimulate, via P-selectin, leukocyte reactive oxygen species production in whole blood. 26 In addition, raised expression of P-selectin reflects platelet activation involving secretion of a broad range of adhesive proteins, procoagulants, cytokines, and growth factors stored in the ␣-granules.…”
mentioning
confidence: 99%
“…16 Several studies indicate that P-selectin mediates adhesion and recruitment of leukocytes to activated platelets, exerts procoagulant activity, and facilitates atherosclerotic development. 14,17 Received In this study, we evaluated the interaction between C pneumoniae and human platelets and found that C pneumoniae binds to platelets and effectively stimulates aggregation, secretion, and surface expression of P-selectin. These observations introduce new possible mechanisms involved in the development of cardiovascular diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation